An Artificial Intelligence ChatGPT-Based Approach for Qibla Identification: Implementation and Analysis - Aziz, Saiful (UIN Sunan Kalijaga, 2024)
The integration of Artificial Intelligence (AI) into religious practices, particularly in determining the qibla direction, offers both opportunities and challenges. While AI tools such as ChatGPT provide high accuracy and efficiency, their acceptance among religious adherents remains uncertain due to concerns over tradition and religious principles. This study aims to evaluate the feasibility and accuracy of ChatGPT-4 in determining the qibla direction compared to traditional methods. A mixed-methods approach was employed, utilizing the principles of Spherical Trigonometry as the primary approach for qibla determination. The accuracy of AI-predicted qibla directions was verified through two different validation techniques: direct measurement using Mizwala for mosques located in Java and Google Earth for indirect validation in mosques outside Java. Statistical analysis, including mean error calculation and standard deviation, demonstrated ChatGPT-4’s exceptionally low average deviation of 0°0’0.026”, confirming its potential as an effective and efficient alternative. However, qualitative insights from mosque administrators highlight concerns about AI’s alignment with religious values and community trust. The study emphasizes that successful AI integration in religious practices requires a balance between preserving tradition and embracing innovation. These findings contribute to ongoing discussions on AI's role in religious contexts, advocating collaboration among religious scholars, technologists, and community leaders. Ultimately, this research successfully bridges the gap between traditional qibla determination methods and AI-based technology, ensuring that technological advancements remain aligned with religious principles. Integrasi Artificial Intelligence (AI) dalam praktik keagamaan, khususnya dalam penentuan arah kiblat, menghadirkan peluang sekaligus tantangan. Meskipun AI seperti ChatGPT menawarkan akurasi dan efisiensi yang tinggi, penerimaannya di kalangan penganut agama masih menghadapi kendala karena pertimbangan tradisi dan prinsip keagamaan. Penelitian ini bertujuan untuk mengevaluasi kelayakan dan akurasi ChatGPT-4 dalam menentukan arah kiblat dibandingkan dengan metode tradisional. Pendekatan metode campuran diterapkan dengan menggunakan prinsip Spherical Trigonometry sebagai pendekatan utama dalam menentukan arah kiblat. Akurasi prediksi arah kiblat yang dihasilkan oleh AI diverifikasi melalui dua teknik validasi yang berbeda: pengukuran langsung menggunakan Mizwala untuk masjid yang berlokasi di Jawa, serta validasi tidak langsung menggunakan Google Earth untuk masjid di luar Jawa. Analisis statistik, termasuk perhitungan rata-rata kesalahan dan deviasi standar, menunjukkan bahwa ChatGPT-4 memiliki deviasi rata-rata sangat rendah sebesar 0°0’0.026”, yang menunjukkan potensinya sebagai alternatif yang efektif dan efisien. Namun, wawasan kualitatif dari pengelola masjid mengungkapkan kekhawatiran terkait kesesuaian AI dengan nilai-nilai keagamaan dan kepercayaan masyarakat. Penelitian ini menegaskan bahwa keberhasilan integrasi AI dalam praktik keagamaan memerlukan keseimbangan antara pelestarian tradisi dan inovasi. Temuan ini berkontribusi pada diskusi yang sedang berlangsung mengenai peran AI dalam praktik keagamaan, mendorong kolaborasi antara ulama, ahli teknologi, dan tokoh masyarakat. Pada akhirnya, penelitian ini berhasil menjembatani kesenjangan antara metode tradisional dalam penentuan arah kiblat dengan teknologi berbasis AI, memastikan bahwa kemajuan teknologi tetap selaras dengan prinsip keagamaan.